Effects of playing three matches consecutive days in U16-U19 soccer players’ vertical jump, rate of perceived exertion and wellness - Moisés Falces Prieto; Javier Raya González; Eduardo Sáez de Villarreal Sáez; Ricardo Martín Moya; Samuel López Mariscal; Francisco Tomás González Fernández (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The objective of this study was to analyze the effect of playing several friendly matches on consecutive days affects neuromuscular fatigue evaluated with countermovement jump (CMJ), session rate of perceived effort (sRPE) and wellness in young male soccer players. Participants: Forty-four young male soccer players from Under 16 (U16) (N= 23; age: 14.70 ± 0.48 years) and U19 (N= 19; age: 17.63 ± 0.52 years) participated in this study. Method: The evaluation of CMJ and Wellness was carried out pre-and post-match. sRPE was recorded 30 minutes after the end of each game. Effect sizes (ES) were calculated using Cohen’s and statistical significance was set at p < 0.05. Results: [U16 group]: differences between CMJ values after the last match and first (p < 0.001) and second (p < 0.001) matches. Differences in fatigue, soreness and stress (p<0.05) were observed. [U19 group]: Differences in CMJ were observed when baseline values were compared with post-match values (p < 0.001) and also when the last match were compared to the first (p < 0.001) and the second (p < 0.001) matches. We only noticed differences between the second and third matches were observed in sleep, stress and humor variables (p < 0.05). Conclusion: In this scenario of competitive tournaments in young players, it is important for fitness coaches to propose practical solutions for reducing the accumulation of fatigue, since this could influence the state of well-being and physical performance of players, and the possible increase on injuries.